Purchasing behavior on foreign and local branded clothing among selected female college students in Metro Manila - Molinyawe, Michell Z.; Bantang, Joanne R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
At present, the fashion industry continuous to boom in the market and one of their popular target markets is the Generation Z who are described to have great purchasing power Geller 2015. In this study, the researcher examined the purchasing practices of a group of female college students on foreign and local branded clothing. Specifically, it identified the clothing purchasing patterns, the level of agreement in the ranking of a predetermined set of criteria as follows price, quality comfortability uniqueness trendiness status symbol stylistic design, wide range of choices and interesting fabric. In addition local and the foreign clothing brands were compared according to the set of criteria. he result of this study showed that in the past six months respondents had an average of six purchases with an average of eight pieces of clothes bought each time. The top reason cited for buying clothes is to have something new to wear for an event and or special occasion particularly for the Christmas and New Year celebration. With regard to the criteria considered in purchasing clothes, results show the following ranking from most to least considered quality price trendiness brand image brand popularity, peer influence, parents influence, social responsibility country manufacturer status symbol national identity and religion. Statistical tests further show the respondents agree in this order of ranking. In comparing local and foreign brands, the foreign brands in general are perceived to be better compared to local brands. Although, local brands are not much behind in terms of acceptability. Among the criteria considered foreign brand are perceived and evaluated to have better stylistic design and status symbol compared to the local brands. The only category where the local brands have an advantage is in terms of affordability. This is the local brands competitive advantage since price is the second considered factor in buying products.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: College students as consumers -- Philippines; Consumers -- Attitudes